LEGAL NATURE AND FEATURES OF DOMESTIC MEDICAL AND HEALTH TOURISM (Bulletin of criminological association of Ukraine, 2025)
This scientific article is devoted to clarifying the peculiarities of legal regulation of domestic medical and health tourism in Ukraine. Scientific approaches to the legal regulation of medical tourism are examined, and the provisions of current legislation in the field of tourism, health care and resort business, which determine the legal basis for the activities of sanatorium and resort establishments providing medical and health services, are analysed. The author proposes a definition of domestic medical and health tourism as the provision of medical, health, rehabilitation and/or recreational services to individuals on the basis of a civil law contract in sanatorium and resort establishments in Ukraine. The peculiarities of the legal regulation of domestic medical and health tourism are identified, as well as the peculiarities of the legal status of sanatorium and resort establishments that can operate in the organisational and legal form of non-commercial enterprises or institutions of state, communal or private ownership. It is emphasised that sanatorium and resort establishments must obtain a licence to carry out economic activities. At the same time, it is pointed out that there are no special licensing requirements in the legislation for them to carry out economic activities in the field of medical practice. The author's vision of a contract for the provision of medical and health services is formulated, which is proposed to be understood as an agreement (contract, memorandum) between a sanatorium-resort institution and a natural or legal person, under which the provider undertakes to provide medical, health, rehabilitation and/or recreational services to the recipient on a paid, free or compensated basis. The essential terms of such an agreement are defined, in particular the subject matter of the agreement with a list of medical and health services, their quality, cost and term of provision. The possibility of including terms and conditions for the provision of medical and health services in a sanatorium-resort facility in a tourist service agreement between a client and a tour operator is justified. A proposal has been made to improve the regulatory framework by developing and approving licensing conditions for the provision of such services, as well as by legislating the terms of the relevant agreement in the Law of Ukraine ‘On Resorts’ or the Law of Ukraine ‘On Tourism’. Prospects for further research in the field of legal support for domestic medical and health tourism have been identified.
Keywords: tourism; medical tourism; medical and health tourism; legal regulation; medical services; health care; service agreement; licensing; contract providing for tourist services